Analysis of Medical Tourism for Cardiovascular Diseases - Catalina Liliana Andrei; Gabriela Tigu; Raluca Mariana Dragoescu; Crina Julieta Sinescu (Amfiteatru Economic)
Increasing costs of treatments have led to the apparition of the medical tourism. Patients in high-income countries seek to solve their health problems in developing countries where the cost of medical treatment is much lower. This cost difference has led to the medical tourism industry that is currently estimated with an annual growth rate of about 20%. Cardiovascular diseases are a leading cause of death worldwide. The high cost of treating these diseases cause many patients to seek treatment options abroad. This paper presents an analysis of the medical tourism industry highlighting the factors that led to its development, barriers to medical tourism, and the economic impact of this industry. Although Romania has highly appreciated doctors it hasn’t achieved yet the high level of other developing countries where medical tourism is more intense. Spa tourism is still far from Romania’s potential in this area due to the very small investments and the lack of necessary infrastructure. Using statistical and econometric techniques we examined key health indicators in Romania showing the lack of correlation between the prevalence of cardiovascular diseases, the development of the endowment of the health system in Romania, expenditures on health care and evolution of the number of foreign tourists coming to Romania to treat these diseases. We used statistical data series provided by N.S.I. that were processed using Eviews. We also tested whether there is a causal relationship in the Granger sense between the percentage of GDP allocated to the health care system and the number of nights spent by foreign tourists in resorts in Romania or the number of arrivals of foreign tourists.